The networked public sphere - Friedland, Lewis A. (Javnost (Ljubljana), 2006)
Habermas's late theory of the public sphere is fundamentally about democracy and growing complexity. The network form is at the core of growing complexity, and the centrality of networks in the economy, political system, civil society, and the lifeworld calls for revisions in central theoretical assumptions about the structure of the public sphere. We argue that in order to maintain Habermas's larger democratic project, we will have to rethink theoretical assumptions linked to its neo-Parsonsian systems theoretical foundations and to systematically integrate new network forms of social life into theory.
Keywords: javnost; javna sfera; democracy; demokracija; civil society; civilna družba; social psychology; socialna psihologija